Exploring English Varieties Used by Indonesian Employees: A Linguistic Perspective - Waode Hanafiah; Nining Syafitri; Sanaria Maneba; Baharudin Adu (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
This research explores the common linguistic features found in the spoken English of Indonesian employees in corporate settings, focusing on grammatical, pronunciation, and vocabulary aspects. The primary objective of this research is to identify and analyze the errors made by Indonesian employees when using English in professional contexts. The research utilizes qualitative methods, involving interviews with employees from various corporate sectors, analyzing their spoken English for common linguistic patterns. The research finds that significant grammatical errors include the omission of plural noun markers (-s/-es), incorrect usage of auxiliary verbs, and the overuse of "to be" in present sentences. Pronunciation errors, such as mispronouncing the ‘v’ sound as ‘f’, and the tendency to apply Indonesian pronunciation patterns, were also prevalent. Additionally, vocabulary usage showed signs of direct translation from Indonesian, resulting in inappropriate word choices. The findings highlight the influence of native language structures on English proficiency, particularly in formal communication. This research emphasizes the need for tailored language training to address these specific challenges, including focused grammar, pronunciation, and vocabulary exercises. It is suggested that such interventions would improve the clarity and effectiveness of English communication among Indonesian employees in the corporate environment. Future researches may further explore sociolinguistic factors and evaluate the efficacy of proposed language improvement programs.